Green Skills Understanding of Agricultural Vocational School Teachers around West Java Indonesia - Handayani, Mustika Nuramalia; Ali, Mohammad; Wahyudin, Dinn; Mukhidin, Mukhidin (Universitas Pendidikan Indonesia, 2020)
This study investigated understanding of agricultural vocational school teachers about green skills and its entity in the curriculum. Data were gathered through survey of teachers from fifteen agricultural vocational high school of agricultural food processing technology study program in West Java Province, Indonesia regarding their understanding about green skills. The results showed that the teachers had less knowledge of green skills, limited to environmental issues. However, they agreed that students needed to be equipped with green skills. The entity of green skills has not been stated explicitly in the curriculum of agricultural vocational school. However, the teachers argued that green skills could be embedded in the subjects of the existing curriculum. The findings of this preliminary study indicated the need to increase teacher understanding of green skills and curriculum development in agricultural vocational schools to meet industrial needs in order to support sustainable development in accordance with the UNESCO strategy for vocational education.